Silicone dielectric elastomer actuator in oil immersion - Pham, Minh Thao. (2013)
Dielectric elastomer actuators, whose actuation mechanism involves mainly Maxwell stress, has been proven to be potential for numerous applications in terms of their performance, weight and simplicity. The finding of La & Lau on the improvement in electric field strength of VHB4905 DEA in oil immersion is the motivation of this study. Previous studies indicated that immerse the VHB4905 DEA in silicone oil bath helps to maintain the temperature of the active region and increase the breakdown field strength. This study employed the same concept and tested BJB silicone DEA to assess whether it manifest the same improvement as VHB4905 DEA. Single film and multi-film planar DEA were tested in silicone oil; subsequently, the area strain and the breakdown field strength of these samples are determined and compared with samples tested in normal condition (in air). The results indicate that silicone oil improves the breakdown field strength but reduces the area strain of the DEA. Part of the finding conforms to La & Lau’s study, but the silicone film becomes ‘swollen’ due to dielectric oil. This behavior leads to the loss of initial tension and hinders the actuation of the DEA. Furthermore, it is found out that the multi-film configuration exhibits lower actuation strain because the passive outer layers of multi-layer configuration restrict the actuation of the whole DEA.